Anatomical Study of Pigmented Rice Leaves (Oryza sativa L.) Resistant to Blast (Pyricularia grisea Sacc.) Disease - Pingkan Krista Mantiri; Fione Yukita Yalindua (Universitas Sam Ratulangi, 2025)
Pigmented Rice (Oryza sativa L.) is one of Indonesia’s local crops with potential to be developed as a source of healthy food. A major constraint in pigmented rice cultivation is the emergence of the fungus Pyricularia grisea (Sacc.), which causes blast disease. This pathogen attacks the leaves, leading to growth damage and even plant death. All plants inherently possess defense mechanisms against external threats, whether biotic (insects, fungi, bacteria, viruses) or abiotic (environmental stress). These mechanisms involve anatomical response. Previous research identified a pigmented rice variety, Cempo Ireng, that exhibits resistance to blast disease caused by P. grisea. Pigmented rice is also known to contain high levels of phenolic compounds and flavonoids, which contribute to plant defense and coloration. This study aims to determine the total phenolic and flavonoid content in the leaves of blast-resistant and susceptible pigmented rice varieties infected by P. grisea (Sacc.). Two pigmented rice varieties were tested: Cempo Ireng (resistant) and Indmira Hitam (moderately resistant). Control Varieties: Asahan (blast-resistant) and Kencana Bali (susceptible). Based on the results of this study, Cempo Ireng and Asahan showed strong resistance to blast disease, Indmira Hitam exhibited moderate resistance and Kencana Bali was highly susceptible to P. grisea infection. Anatomical observations of leaves using leaf surface section showed differences in structural modification of epidermal thickness, mesophyll thickness and the diameter of vascular bundle, where Cempo Ireng varieties were able to form good epidermal thickness as the initial barrier of defense. The anatomical observations of leaves using SEM showed anatomical differences in trichome density in Cempo Ireng and Asahan leaves which had the highest density compared to other varieties in response to the attack of fungal pathogens.